Psychological screening of adults and young people following the Manchester Arena incident. Issue 5 (September 2019) - French, Paul; Barrett, Alan; Allsopp, Kate; Williams, Richard; Brewin, Chris R.; Hind, Daniel; Sutton, Rebecca; Stancombe, John; Chitsabesan, Prathiba
Abstract : Background: Terrorist attacks have increased globally since the late 1990s with clear evidence of psychological distress across both adults and children and young people (CYP). After the Manchester Arena terrorist attack, the Resilience Hub was established to identify people in need of psychological and psychosocial support. Aims: To examine the severity of symptoms and impact of the programme. Method: The hub offers outreach, screening, clinical telephone triage and facilitation to access evidenced treatments. People were screened for trauma, depression, generalised anxiety and functioning who registered at 3, 6 and 9 months post-incident. Baseline scores were compared between screening groups (first screen at 3, 6 or 9 months) in each cohort (adult, CYP), and within groups to compare scores at 9 months. Results: There were significant differences in adults' baseline scores across screening groups on trauma, depression, anxiety and functioning. There were significant differences in the baseline scores of CYP across screening groups on trauma, depression, generalised anxiety and separation anxiety. Paired samples t -tests demonstrated significant differences between baseline and follow-up scores on all measures for adults in the 3-month screening group, and only depression and functioning measures for adults in the 6-month screening group. Data about CYP in the 3-month screening group, demonstrated significant differences between baseline and follow-up scores on trauma, generalised anxiety and separation anxiety. Conclusions: These findings suggest people who register earlier are less symptomatic and demonstrate greater improvement across a range of psychological measures. Further longitudinal research is necessary to understand changes over time. Declaration of interest: None.